Genetic features of red and green junglefowls and relationship with Indonesian native chickens Sumatera and Kedu Hitam. (December 2016) - Ulfah, Maria; Kawahara-Miki, Ryouka; Farajalllah, Achmad; Muladno, Muladno; Dorshorst, Ben; Martin, Alison; Kono, Tomohiro
Abstract Background More than 2, 500 breeds of chicken are reared throughout the world as a source of eggs or meat and as pets. The primary ancestor of the present domestic chicken is widely believed to be the red junglefowl, although genetic contributions from other junglefowls cannot be excluded entirely. The reference genome for chicken was obtained from a red junglefowl, the genetic purity of which has been debated. There is, at present, insufficient data to resolve these interesting issues. Results In this study, we performed whole-genome sequencing to compare various species and breeds of chicken, including wild red and green junglefowl, as well as the Indonesian native chickens Sumatera and KeduHitam and their respective descendants, the American Black Sumatra and Black Java. The data indicate that wild junglefowls have retained their genetic identity, but the Indonesian and American breeds have not. The Black Sumatra and Black Java are now closely related to each other, suggesting loss of genetic identity after export to the United States. In addition, the results indicate that the red junglefowl used as reference genome is more closely related to domestic chickens and apparently different from other wild red junglefowls. Conclusions This study illuminates the genetic and phylogenetic relationships among these species. It provides a framework for genetic studies in wild junglefowls and native and domestic chicken breeds.